RELATIONSHIP BETWEEN ECOLOGICAL FACTORS AND CAROTENOID CONTENT IN Gracilaria sp. IN THE SILVOFISHERY OF THE NORTH COAST OF CENTRAL JAVA - Swietenia Purnamasari; Rose Dewi; Tjahjo Winanto (Universitas Mataram, 2025)
Gracilaria sp. is a seaweed with high economic value and is able to produce natural pigments in the form of carotenoids. The purpose of this study was to determine the value of the carotenoid content of Gracilaria sp., to determine the ecological conditions (physicochemical) of the water and to determine the relationship between these measurement variables. The method used was a survey method with a spatial approach (4 stations) and temporal (4 seasons). For the carotenoid variable, Gracilaria sp. was measured using a UV-Vis 1800V spectrophotometer. This study used Principal Component Analysis to determine the relationship between ecological factors and the carotenoid content of Gracilaria sp. The carotenoid content obtained spatially ranged from 14.03-31.10 mg/L and temporally 3.86-35.52 mg/L. The ecological conditions of the silvofishery area spatio-temporally have conditions that can be tolerated for the formation of carotenoids. The relationship between carotenoid content and ecological factors spatially produces an eigenvalue of 84.82% with F1 60.82% and F2 24.00%, with characteristics influenced by anthropogenic. Temporally produces an eigenvalue of 80.26% with F1 42.50% and F2 37.76%, with characteristics influenced by rainfall.